2014
DOI: 10.1371/journal.pone.0109996
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Heparin and Unfractionated Heparin Decrease Th-1, 2, and 17 Expressions

Abstract: BackgroundWe evaluated the effects of T helper cell differentiation in a mite-allergic animal model treated with inhaled heparins of different molecular weight.MethodBALB/c mice were divided into four groups: 1. Control, 2. Mite intratracheal (mIT), 3. Inhaled heparin (hIN), 4. Inhaled low-molecular-weight heparin (lmwhIN). Groups 2, 3, and 4 were sensitized twice with Der p allergen subcutaneously on day 1 and day 8. Der p allergen was administered intratracheally on day 15. Groups 3 and 4 were treated with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
2
8
0
2
Order By: Relevance
“…The effect on GATA-3 may in turn explain the simultaneous effects of S-NACH treatment on IL-4, IL-5, and IL-13 in mice acutely or chronically challenged with OVA. These results are consistent with those reported by Huang et al [ 26 ] using a house dust mite extract-based model of asthma. Unlike that study, which reported a modulatory effect of LMWH on both Th1 and Th2 cytokines, our study showed that S-NACH was more selective against Th2 cytokines because it did not affect IFNγ levels after OVA exposure either acutely or chronically.…”
Section: Discussionsupporting
confidence: 93%
“…The effect on GATA-3 may in turn explain the simultaneous effects of S-NACH treatment on IL-4, IL-5, and IL-13 in mice acutely or chronically challenged with OVA. These results are consistent with those reported by Huang et al [ 26 ] using a house dust mite extract-based model of asthma. Unlike that study, which reported a modulatory effect of LMWH on both Th1 and Th2 cytokines, our study showed that S-NACH was more selective against Th2 cytokines because it did not affect IFNγ levels after OVA exposure either acutely or chronically.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that heparin has inhibitory effects on T cell proliferation in MLRs [4,38] and natural killer cell cytotoxicity [39]. Reduced differentiation of Th1, Th2, and Th17 in the spleen by both heparin and LMWH treatment has also been reported [40]. The results of these studies support the hypothesis that heparin promotes T reg induction.…”
supporting
confidence: 65%
“…As necrosis factor-alpha [145,190,234]. However, the current study for the first time demonstrated that enoxaparin can significantly inhibit the release of IL-6 and IL-8 from the stimulated lung epithelial cells.…”
Section: Effect Of Enoxaparin On Il-6 and Il-8 Releasementioning
confidence: 47%